DAMPAK PEMBERIAN KALIUM DAN CEKAMAN KEKERINGAN TERHADAP SERAPAN HARA DAN PRODUKSI BIOMASSA BIBIT KELAPA SAWIT (Elaeis gueenensis Jacq.) - Wan Riski Fauzi; Eka Tarwaca Susila Putra (Pusat Penelitian Kelapa Sawit, 2019)
Droght stress is the main limiting factor on growth and production of oil palm. Beside used tolerance planting materials, increasing nutrient status especially potassium also influences increasing plant tolerance to drought stress. This research was a simulation study in a greenhouse to determine the effect of potassium and drought stress on oil palm seedling. The research was conducted in Desa Madurejo, Kecamatan Prambanan, Kabupaten Sleman, Region of Yogyakarta Indonesia by random complete block design. The treatment consists of two factors, first factor were potassium factor consist of 0%, 50%, 150%, and 200% standart dosage and second factor were drought stress consist of three levels, field capacity (FTSW 1), moderate drought stress (FTSW 0.35) and severe (FTSW 0.15) with three replications. The results showed that fertilizing potassium increased the content and uptake of K and Cl in plants, increased the uptake of Mg roots, reduce the N content of the roots and reduce the content of Ca and Mg in plant canopy. Drought stress had an impact on decreasing the content and uptake of N, P, and Cl in plants as well as decreasing the dry weight of plant biomass. The provision of Potassium has not affected the production of biomass of oil palm seedlings in drought conditions.